Karakteristik Pasien Hipertensi Dalam Upaya Pengendalian Hipertensi di Poliklinik Penyakit Dalam Rumah Sakit - Zikran Zikran; Romy Suwahyu (Jurnal Sains dan Kesehatan, 2024)
Hypertension is still a health problem in the world, including in Indonesia. The increasing prevalence of hypertension is because there are still many hypertension patients who have not received treatment or who have been treated. Hypertension is not controlled properly and correctly and will have an impact on complications, this can increase morbidity and mortality. Hypertension patients are expected to be able to control hypertension properly and correctly with a good lifestyle according to recommendations to prevent hypertension complications. The purpose of this study was to determine the characteristics of hypertension patients in efforts to control hypertension in the Internal Medicine Polyclinic of the Hospital. This type of research uses a descriptive survey and a cross-sectional research approach. The results of this study show that the characteristics of respondents are mostly male compared to women, most are 45-64 years old, have excess body weight, have high school and college education, have civil servant jobs and are retired civil servants, have a history of hypertension from their families, have a duration of hypertension 0-1 years and a duration of hypertension treatment 0-1 years. It is recommended for hypertension sufferers to control hypertension and other researchers to conduct research with wider variables.